Pediatric Nephrology Sixth Completely Revised, Updated and Enlarged Edition - Avner, Ellis; Harmon, William; Niaudet, Patrick; Yoshikawa, Norishige; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2009)
Through 5 editions, Pediatric Nephrology has become the standard reference text for students, trainees, practicing physicians (Pediatricians, Nephrologists, Internists, and Urologists), sub-specialists, and allied health professionals seeking information about Children$1 (Bs Kidney Diseases. It is global in perspective and reflects the international group of editors, who are well-recognized world$1 (Bs experts in Pediatric Nephrology. In a single text, the development of kidney structure and function is followed by detailed and comprehensive chapters on all childhood kidney diseases. These chapters, grouped by major disease categories, utilize molecular and cellular pathophysiology of disease to provide unique and comprehensive information of the current state of the art on all known childhood kidney diseases. Each chapter makes new genetic information easily understandable for the practitioner, and uses many algorithms and diagrams to describe appropriate clinical evaluation of symptoms, differential diagnosis, specific diagnostics, and currently available therapies. The text is not only found in University/Hospital libraries, but on the shelves of sub-specialists, pediatricians, internists, urologists, and extensively in the clinics where it is used during clinical encounters with childhood kidney disease.s
Keywords: Medicine; General practice (Medicine).; Internal medicine; Nephrology; Pediatrics; Urology; Medicine & Public Health; Nephrology; Pediatrics; Urology; Internal Medicine; General Practice / Family Medicine; Electronic books